Increasing Mutual Cooperation Values Using the Scramble Method in Class X Students of SMA Negeri 1 Palu - DM, Sya'ban Abdullah; Afni, Nur (Journal of Education Method and Learning Strategy, 2023)
This class action research was carried out in class . with the aim of improving students' mutual cooperation skills during the learning process using the scramble type cooperative model, this type of research is descriptive quantitative, in the initial test students get a score of 2.65 or 66%, during the learning process it is seen that students still need to increase in collaboration and also communication/discussion of the problems being faced, in the implementation of the first cycle students see an increase in students who are able to discuss and exchange opinions to agree on joint decisions. The results of the student mutual cooperation skills questionnaire increased to 3.16 or 79%, the shortcoming in the first cycle was that the coordination of group members in compiling keywords still needed to be improved, in the second cycle changes were made to student activities in compiling keywords where the group leader was appointed to coordinate group members in the process of compiling keywords, the results of the second cycle questionnaire showed an increase to 3.54 or 88%.